Stop Disasters 2.0: Video Games as Tools for Disaster Risk Reduction. Issue 2 (August 2016) - Gampell, Anthony Viennaminovich; Gaillard, JC
Increasingly, international organisations (e.g. UNESCO, UNISDR), governments (e.g. Canada), and non-government organisations (NGOs) (e.g. Save the Children, Christian Aid) and researchers use video games to raise disaster and disaster risk reduction (DRR) awareness. Yet, there is a paucity of studies on these games in the disaster literature. This article presents a typology specifically designed to deconstruct both disaster awareness building and mainstream disaster orientated video games, identifying how games like Stop Disasters, Disaster Watch, Inside Haiti, Earthquake Response, Fallout and SimCity instil disaster awareness, portray hazards, vulnerabilities, capacities, disasters and DRR. The article also touches upon ideas of game content, player motivation, skill building and social interaction in the context of disaster themed video games. The findings suggest video games have the potential to be positive tools to reinforce messages surrounding DRR, though further research is necessary. This article sets an agenda for future research.